Effect of Particle Size on the Wear Property of Magnetorheological Fluid - Qiuxiang Zhang; Xinhua Liu; Yankun Ren; Lifeng Wang; Yuan Hu (Advances in Materials Science and Engineering)
Aiming to study the effect of particle size on the wear property of magnetorheological fluid (MRF), experiment materials, preparation process, and test methods are elaborated, and three different MRF samples consisting of particles of different size are prepared. Test experiments are carried out and the effect of particle size on the wear property of MRF is discussed. Moreover, the microstructures of particles extracted from MRF obtained before and after the wear experiments are observed by scanning electron microscope (SEM). Experimental results show that the particle size has a significant effect on wear property of MRF. Furthermore, the MRF with particles of 1.5–2.8 μm diameter on average is good for the requirement of engineering applications.